A Dynamic Motion Control Technique for Human-like Articulated Figures - Oshita, Masaki; Makinouchi, Akifumi (Computer graphics forum, 2001)
This paper presents a dynamic motion control technique for human‐like articulated figures in a physically based character animation system. This method controls a figure such that the figure tracks input motion specified by a user. When environmental physical input such as an external force or a collision impulse are applied to the figure, this method generates dynamically changing motion in response to the physical input. We have introduced comfort and balance control to compute the angular acceleration of the figure's joints. Our algorithm controls the several parts of a human‐like articulated figure separetely through the minimum number of degrees‐of‐freedom. Using this approach, our algorithm simulates realistic human motions at efficient computational cost. Unlike existing dynamic simulation systems, our method assumes that input motion is already realistic, and is aimed at dynamically changing the input motion in real‐time only when unexpected physical input is applied to the figure. As such, our method works efficiently in the framework of current computer games.